Right To Parenthood- A Left Crevice in Surrogacy Regulation Act 2021: Re view (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Surrogacy refers to a practice whereby one woman bears and gives birth to a child  for an intended couple with the intention of handing over such a child to the intended  couple after birth. The right to parenthood, often referred to as the right to procreate  or reproductive rights, is a fundamental human right. It encompasses individuals’  ability to make decisions about having and raising children without undue interference  from the state or other entities. This right is rooted in various legal and constitutional  principles including the right to privacy, family autonomy, and personal liberty. In  this case, we have tried to scrutinize the laws of the surrogacy act and how they  impacted the life of an intending couple. The Supreme Court has protected the right  of parenthood of a woman suffering from a rare medical condition by staying the  operation of a law that threatened to wreck her hopes to become a mother through  surrogacy
Keywords: Surrogacy; Intending Couple; Right to Parenthood; Supreme Court